HER-2 overexpressing breast cancer during pregnancy: a case report and literature review - Li, Si; Huang, Tuoshu; Feng, Mujin; Deng, Minjun; Chen, Xiyu; Li, Xinning; Mo, Dan (Frontiers in Oncology, 2026)
BackgroundBreast cancer during pregnancy (PrBC) is rare but increasingly reported due to delayed childbearing, widespread assisted reproduction, and younger onset of breast cancer. Among these, HER2-overexpressing subtypes pose particular clinical challenges in balancing effective oncologic control with fetal safety. It requires a delicate balance between optimizing maternal oncologic outcomes and ensuring fetal safety.Case presentationWe report the case of a 33-year-old woman diagnosed with HER-2 overexpressing invasive ductal carcinoma of the right breast at 16 weeks of gestation. Driven by a strong desire to continue the pregnancy, the patient, in consultation with a multidisciplinary team, opted for neoadjuvant chemotherapy. From 17 to 31 weeks’ gestation, she received four cycles of epirubicin and cyclophosphamide, followed by one cycle of nab-paclitaxel, achieving a partial response. At 37 weeks, she underwent a successful vaginal delivery, giving birth to a healthy female infant. Postpartum, she continued her neoadjuvant treatment with three cycles of nab-paclitaxel plus dual anti-HER2 therapy (trastuzumab and pertuzumab). After completing the full neoadjuvant regimen, she underwent breast-conserving surgery, and pathology confirmed a complete response. Her postoperative treatment included adjuvant dual anti-HER2 therapy and whole-breast radiotherapy. At the last follow-up (18 months post-delivery), the mother showed no signs of recurrence, and the child exhibited normal growth and neurodevelopment.ConclusionsThis case demonstrates that with careful multidisciplinary planning and individualized treatment strategies, it is feasible to achieve both successful maternal oncologic control and the delivery of a healthy baby in patients with HER-2 overexpressing breast cancer during pregnancy. This case contributes valuable evidence to the management of this complex clinical scenario.